2014
DOI: 10.1002/j.0022-0337.2014.78.6.tb05747.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Learning Styles of Saudi Dental Students Using Kolb's Learning Style Inventory

Abstract: Experiential learning theory (ELT), a theory developed by David

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 14 publications
(21 reference statements)
8
27
0
1
Order By: Relevance
“…In this study male and female students were not different in their learning styles, which was similar to the results of other studies ( AL-Qahtani & Al-Gahtani, 2014 ; Ghaffari et al, 2013 ; Meyari et al, 2010 ; Saif & Hosseini Lorgani, 2001 ). Moreover, this study showed that most of the participants’ learning style was Assimilating (53.1%); which is concordant with the findings of studies conducted on medical students ( Azizi et al, 2002 ; Ghaffari et al, 2013 ; Saif & Hosseini Lorgani, 2001 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study male and female students were not different in their learning styles, which was similar to the results of other studies ( AL-Qahtani & Al-Gahtani, 2014 ; Ghaffari et al, 2013 ; Meyari et al, 2010 ; Saif & Hosseini Lorgani, 2001 ). Moreover, this study showed that most of the participants’ learning style was Assimilating (53.1%); which is concordant with the findings of studies conducted on medical students ( Azizi et al, 2002 ; Ghaffari et al, 2013 ; Saif & Hosseini Lorgani, 2001 ).…”
Section: Discussionsupporting
confidence: 92%
“…Also, Hopkins believes that Kolb does not explain the nature of experiential process ( Hopkins, 1993 ); his theory is popular due to being easy to use ( Armstrong & Parsa-Parsi, 2005 ). However, based on this theory, several studies have been done on different learners all around the world ( Alcota, Muñoz, & González, 2011 ; ALQahtani & Al-Gahtani, 2014 ; Bitran, Zúñiga, Pedrals, Padilla, & Mena, 2012 ; Fang, 2002 ; Ghaffari et al, 2013 ; Meyari et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students learn through a variety of approaches; they can assimilate and process a several types of information in different ways 9 . A learning style can be described as a set of cognitive, emotional and physiological features that can be used as indicators of how a person can learn 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the clumps of science, the subject of research is a student of the Faculty of Education Unesa, which based on the clumps of science into the group of educational science. In contrast to the results of the above research, students from the arts, history, psychology and literature departments prefer divergent learning styles [23], dentistry students [31]. The differences in the results of the above studies, proving that learning styles are flexible [29], are not related to the selected courses or courses.…”
Section: Resultsmentioning
confidence: 68%